2012
DOI: 10.7314/apjcp.2012.13.1.041
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Stem Cell Antigen Single Nucleotide Polymorphisms Influence Risk of Estrogen Receptor Negative Breast Cancer in Korean Females

Abstract: Introduction: Breast cancer is the second leading cancer in Korean women. To assess potential genetic associations between the prostate stem cell antigen (PSCA) gene in the chromosome 8q24 locus and breast cancer risk in Korean women, 13 SNPs were selected and associations with breast cancer risk were analyzed with reference to hormone receptor (HR) and menopausal status. Methods:We analyzed DNA extracted from buffy coat from 456 patients and 461 control samples, using matrix-assisted laser desorption/ionizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
0
20
1
Order By: Relevance
“…Overall, there were 32 studies investigating the association between PSCA rs2294008 C>T polymorphism and cancer susceptibility, consisting of 30028 cases and 38765 controls [8, 9, 14-35, 39-43], and 14 studies performed on the relation between PSCA rs2976392 G>A polymorphism and overall cancer susceptibility, with 8190 cases and 7176 controls [8, 14-17, 19, 24, 29, 36-39, 43]. The main characteristics of the studies included in this meta-analysis were summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, there were 32 studies investigating the association between PSCA rs2294008 C>T polymorphism and cancer susceptibility, consisting of 30028 cases and 38765 controls [8, 9, 14-35, 39-43], and 14 studies performed on the relation between PSCA rs2976392 G>A polymorphism and overall cancer susceptibility, with 8190 cases and 7176 controls [8, 14-17, 19, 24, 29, 36-39, 43]. The main characteristics of the studies included in this meta-analysis were summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The studied cancer type included gastric cancer [8, 14-17, 20-22, 25, 26, 31, 32, 34, 39, 41-43], bladder cancer [9, 18, 23, 28, 35, 40], prostate cancer [19], esophageal cancer [20, 33], breast cancer [24], colorectal cancer [27], and gallbladder cancer [29, 30]. In term of ethnicity, 21 studies were performed among Asians, 10 studies among Caucasians, and one study among Africans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that since the PSCA may have significantly higher expression levels in males than in females, decrease in PSCA expression levels due to the SNPs in PSCA would have more significant impact on the function of this tumor suppressor in females than in males (Wu et al, 2009a). Another study showed a significant association between PSCA SNPs and breast cancer susceptibility in Korean women, particularly those who were pre-menopausal with an estrogen receptor negative tumor status (Kim et al, 2012).…”
Section: Haplotypesmentioning
confidence: 96%
“…PSCA, involving either change in protein expression or through association with the polymorphism in the PSCA gene, may act as an oncogene; play a role in tumor progression in some cancers while tumor suppressor gene in others (Saeki et al, 2010;Smith et al, 2012). Genetic variants of PSCA have been found to be strongly associated with the risk for cancers of the breast (Kim et al, 2012), bladder (Rothman et al, 2010), duodenal (Tanikawa et al, 2012) and stomach (Qiao and Feng, 2012) etc. Recently, PSCA has been shown to be involved in GBC development (Ono et al, 2012) and its SNP rs2294008, is also considered a potential genetic risk factor in GBC.…”
Section: Introductionmentioning
confidence: 97%